THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE (Empirical Study on Companies Included in the IDX SRI KEHATI ESG Sector Leader Index) - Fransiskus Benediktus Carolus Dendi Uma (International Journal of Management, Business, and Social Sciences, 2023)
This research aims to analyze the influence of Corporate Social Responsibility on company value on the Indonesian Stock Exchange. The object of this research is companies that are members of the IDX SRI KEHATI ESG Sector Leader index in 2015-2020. The sampling technique is purposive sampling. The data used is secondary data which was analyzed using panel data regression. This research is quantitative research. The analysis tool uses the Classic Assumption Test, Model Test and Hypothesis Test with Eviews 12 software. The research result shows that Corporate Social Responsibility influences company value.